Kedisiplinan dan Kinerja Karyawan: Studi Kasus di Bengkel Gandi Jaya Motor Jombang - Affan, Mohamad Setia Maulana Affandi; Andriani, Andriani (Lembaga Pengembangan Kinerja Dosen, 2026)
Work discipline is a crucial element in improving employee performance, particularly in the Micro, Small, and Medium Enterprises (MSME) sector such as automotive workshops, which often face managerial and structural challenges. This study aims to explore the understanding, implementation, and influence of work discipline on employee performance at Gandi Jaya Motor Workshop, Jombang, within a local context characterized by religious values and informal work culture. The research employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, and were analyzed thematically. The findings reveal that work discipline is perceived as a form of personal responsibility driven by leadership example and religious values, rather than by formal systems alone. External factors such as limited infrastructure and the absence of a structured HR evaluation system also affect performance effectiveness. These findings expand the scope of Work Discipline and Employee Performance theories by incorporating social and cultural dimensions as determinants of work behavior. The study concludes by emphasizing the need for a humanistic approach to HR management in MSMEs and recommends further exploration with broader participant coverage and more diverse methodological approaches.